On closeness of the sum of n subspaces of a Hilbert space - Feshchenko, I. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We give necessary and sufficient conditions for the sum of subspaces H_1,..., H_n, n ≥ 2, of a Hilbert space H to be a subspace and present various properties of n-tuples of subspaces with closed sum.